USING OF MATERIAL DIDACTICAL FACILITIES IN TECHNICAL EDUCATION - HÔRECKÝ, Ján (Trends in education, 2008)
The aim of this article is to show the ways of using material didactical Instruments on the Technical Education lessons.
Keywords: Technical Education; material didactical facilities; computer